1990
DOI: 10.1104/pp.94.4.1770
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ethylene on the Kinetics of Curvature and Auxin Redistribution in Gravistimulated Roots of Zea mays

Abstract: We tested the involvement of ethylene in maize (Zea mays L.) root gravitropism by measuring the kinetics of curvature and lateral auxin movement in roots treated with ethylene, inhibitors of ethylene synthesis, or inhibitors of ethylene action. In the presence of ethylene the latent period of gravitropic curvature appeared to be increased somewhat. However, ethylene-treated roots continued to curve after control roots had reached their final angle of curvature. Consequently, maximum curvature in the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
54
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 11 publications
1
54
0
Order By: Relevance
“…If flavonoid expression is under the same light control in maize seedlings as in Arabidopsis seedlings (Wade et al, 2001;Muller et al, 2005), their dark-grown seedlings may mimic our tt4 mutants with an absence of flavonoid synthesis. This complex role of ethylene, with both stimulatory and inhibitory effects on root gravitropism, may explain the contradictory conclusions in the literature on the question of whether ethylene regulates gravitropism (Wheeler and Salisbury, 1981;Kaufman et al, 1985;Harrison and Pickard, 1986;Wheeler et al, 1986;Lee et al, 1990;Woltering, 1991;Kiss et al, 1999;Madlung et al, 1999). Because both ethylene and flavonoid synthesis are regulated by light, nutrients, and other environmental signals (WinkelShirley, 2002;Vandenbussche et al, 2003), it is likely that these contradictory results come from studies in which the synthesis of these molecules is differentially regulated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…If flavonoid expression is under the same light control in maize seedlings as in Arabidopsis seedlings (Wade et al, 2001;Muller et al, 2005), their dark-grown seedlings may mimic our tt4 mutants with an absence of flavonoid synthesis. This complex role of ethylene, with both stimulatory and inhibitory effects on root gravitropism, may explain the contradictory conclusions in the literature on the question of whether ethylene regulates gravitropism (Wheeler and Salisbury, 1981;Kaufman et al, 1985;Harrison and Pickard, 1986;Wheeler et al, 1986;Lee et al, 1990;Woltering, 1991;Kiss et al, 1999;Madlung et al, 1999). Because both ethylene and flavonoid synthesis are regulated by light, nutrients, and other environmental signals (WinkelShirley, 2002;Vandenbussche et al, 2003), it is likely that these contradictory results come from studies in which the synthesis of these molecules is differentially regulated.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this idea, ethylene reduced polar IAA transport in shoot tissues of several species (Morgan and Gausman, 1966;Suttle, 1988). Additionally, ethylene reduced the lateral redistribution of auxin across gravity-stimulated corn roots (Lee et al, 1990). The agravitropic mutant eir1 is insensitive to ethylene inhibition of root growth and has a defect in a gene encoding a protein linked to auxin efflux (Luschnig et al, 1998).…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…Lateral redistribution of radiolabeled indole-3-acetic acid (IAA) has been measured in both shoots (Parker and Briggs, 1990) and roots (Young et al, 1990;Young and Evans, 1996), and the redistribution of IAA has been shown to precede differential growth (Parker and Briggs, 1990). Other plant hormones, specifically brassinosteroids (Kim et al, 2000), ethylene (Lee et al, 1990;PhilosophHadas et al, 1996;Madlung et al, 1999), cytokinin (Golan et al, 1996), and gibberellic acid (Moore and Dickey, 1985;Rood et al, 1987;Brock and Kaufman, 1988;Chaban et al, 1999) have been shown to also play a role in gravitropism. Reactive oxygen species may function as a downstream component in auxinmediated signal transduction (Joo et al, 2001).…”
mentioning
confidence: 99%